1955
DOI: 10.1149/1.2430000
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Titanium Coatings from Pyrosols

Abstract: It has been found that titanium dispersed in fused salts can be deposited on other metals, especially on copper and iron. l%r example, if a piece of copper sheet is placed in close proximity to a titanium sheet (but not in actual contact) and then the whole is immersed into a fused salt, preferably NaC1 or KC1, titanium will transfer to the copper sheet. The thickness of the titanium layer on the copper increases with temperature and time, approaching a maximum thickness of 0.001-0.007 in. (0.025-0.178 mm). Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1959
1959
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…The reaction mechanism of molten salts including Cu or Co is not clear at this moment. However, the mechanism of deposition of a metal, for example Titanium, from a molten salt was investigated [34][35][36]. The phenomena would provide useful information to discuss the incorporation of Cu or Co atoms into the silicide.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction mechanism of molten salts including Cu or Co is not clear at this moment. However, the mechanism of deposition of a metal, for example Titanium, from a molten salt was investigated [34][35][36]. The phenomena would provide useful information to discuss the incorporation of Cu or Co atoms into the silicide.…”
Section: Resultsmentioning
confidence: 99%
“…It seems, therefore, that the formation of TiL would take place predominantly at the surface of the anode at higher current densities. This TiI~ would tend, however, to be transformed rapidly in presence of KF according to the reaction TiL W 2KF -* TiF~ ~-2KI [3] TiF, (due to reaction [2])…”
Section: May 1959mentioning
confidence: 99%
“…In fact, reaction [3] is very exothermic, and furthermore it was found that the reddish-brown color of TiL did not show up at the end of the electrolysis of the KI-KF bath. To prove reaction [3] by way of similitude, TiI, was added to a molten KF bath, and it was observed that the brown color of TiL vanished to form KI as was established by x-ray diffraction analysis; the violet complex of TiF, and KF identified as K3TiF, was also found.…”
Section: May 1959mentioning
confidence: 99%
See 1 more Smart Citation
“…Electroplating of titanium on base metals in molten salts is desired for some properties, such as improving corrosion resistance, so that many researchers investigated it [1][2][3][4][5][6][7][8][9][10]. However, the practical process of titanium electroplating has not been attained since the mechanism of the electrodeposition of titanium in molten salts is too complicated to control the morphology of the deposits.…”
Section: Introductionmentioning
confidence: 99%